Introduction to RF stealth - Lynch, David (David D.) (Raleigh, NC SciTech Publishing, 2004)
The book reviews developments in the following fields: stealth systems; interceptability parameters and analysis; intercept receivers; stealth waveforms; stealth antennas and radomes; and signal processing.
Electronic reproduction.
Keywords: Low probability of intercept radar; Radar -- Military applications; Signal detection -- Mathematics; Electronic books